Pendidikan Inklusif Berbasis Nilai Islam dalam Menangani Kenakalan Santri: Studi di Pesantren Al-Hassan Rembang - Mustami'ah, Siti Nailul; Najib, Muhammad (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Islamic education in Indonesia faces contemporary challenges, particularly in addressing student misconduct within traditional educational institutions. This research examines the implementation of inclusive education at Al-Hassan Islamic Boarding School in Rembang as an approach to handle student delinquency. The study aims to analyze inclusive educational practices based on Islamic values of wasathiyah and their effectiveness in character building and behavioral correction. Using qualitative methodology with ethnographic approach, data was collected through participant observation, in-depth interviews with school administrators, teachers, and students, as well as documentation analysis. The research reveals that Al-Hassan Islamic Boarding School successfully implements inclusive education by accepting students from diverse backgrounds without discrimination, including those from economically disadvantaged families, orphans, broken homes, and students with learning difficulties. The boarding school employs humanistic and empathetic approaches in handling student misconduct, prioritizing dialogue, mediation, and character development over punitive measures. Key findings indicate that inclusive educational strategies based on Islamic theological values prove more effective in transforming student behavior compared to repressive approaches. The integration of social-emotional programs, individual counseling, and collaborative problem-solving creates a conducive learning environment for holistic character development. The study concludes that inclusive education rooted in Islamic values of justice, compassion, and brotherhood provides a viable alternative model for contemporary Islamic education in Indonesia, demonstrating that traditional Islamic boarding schools can adapt modern educational principles while maintaining their spiritual foundation and cultural authenticity. Keywords: inclusive education, Islamic boarding school, student delinquency, character building, wasathiyah